Klosterfrau-Group Award for Research of Airway Diseases in Childhood 2025 (Klinische Pädiatrie, 2024)
Application starts on June 3, 2024 and ends on November 22, 2024The Klosterfrau Foundation wants to encourage researchers in the field of pediatric respiratory medicine to apply for the prestigious Klosterfrau-Group Award for Research of Airway Diseases in Childhood. The award exists in its 25th year.